Society in his Life Spiritual of Needs Held Place (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the role of spiritual needs in the life of society, the classification of the system of needs, a number of successful scientific researches have been carried out on the socio-philosophical and cultural factors of the development of spiritual needs.